2023
DOI: 10.1108/jcefts-01-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Foreign divestment, economic growth and development in South Africa: an empirical analysis

Abstract: Purpose The purpose of this study is to investigate the effect of foreign direct divestments (FDD) on economic growth and development in South Africa for the period 1991–2019. Design/methodology/approach The non-linear autoregressive distributed lag technique is used for the empirical analysis. Two regression models are specified, one for economic growth and the other for development which is proxied by poverty. Findings The empirical results suggest that foreign divestments are detrimental to both economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Hanyurwumutima and Gumede (2021) found that while public transport expenditure alone did not significantly impact output growth in South Africa's major metropolitan areas from 2003 to 2017, its combination with other social infrastructure had a notable effect. Moreover, Matekenya and Moyo (2023) suggested a negative impact of FDI on economic growth.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Hanyurwumutima and Gumede (2021) found that while public transport expenditure alone did not significantly impact output growth in South Africa's major metropolitan areas from 2003 to 2017, its combination with other social infrastructure had a notable effect. Moreover, Matekenya and Moyo (2023) suggested a negative impact of FDI on economic growth.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Various foreign divestment theories such as the eclectic paradigm, divestiture, institutional-based view, real options and neoclassical, have been employed by scholars to better understand foreign divestment (see Matekenya & Moyo, 2023;Konara & Ganotakis, 2020;Arte & Larimo, 2019;Musshoff, Odening, Schade, Maart-Noelck & Sandri, 2013;Edo & Nnadozie, 2023). The theoretical foundation of this paper is derived from the existing literature on foreign divestment.…”
Section: Conceptual and Theoretical Reviewmentioning
confidence: 99%
“…The theoretical foundation of this paper is derived from the existing literature on foreign divestment. Dunning's eclectic paradigm suggests that multinational enterprises expand overseas through FDI if competitive, location, and internalisation advantages are met (Matekenya & Moyo, 2023). Therefore, Boddewyn (1983) used Dunning's framework to develop a theory on foreign divestment, reversing the above-stated advantages to create a proto-theory on foreign divestment (Matekenya & Moyo, 2023).…”
Section: Conceptual and Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies deal with the effect of FDD on developing countries (for example, Zreik, 2023). Matekenya and Moyo (2023) suggest that FDD is detrimental to both economic growth and development and produce results showing that the adverse effects of FDD outweigh the benefits derived from FDI inflows. They also argue that the literature on the impact of FDD on economic growth needs to cover economic development.…”
Section: Implications For Developing Countriesmentioning
confidence: 99%